Electrolyte Modification for Long‐Life Zn Ion Batteries: Achieved by Methanol Additive - Lin, Xian‐Sen; Wang, Zi‐Rui; Ge, Lin‐Heng; Xu, Jun‐Wei; Ma, Wen‐Qing; Ren, Man‐Man; Liu, Wei‐Liang; Yao, Jin‐Shui; Zhang, Chang‐Bin (ChemElectroChem, 2022)
Although zinc‐ion batteries are regarded as important alternatives for Li‐ion batteries, the dendrite issues and side reactions are major obstacles for their development. Here, inspired by the idea of electrolyte modification, a simple and low‐cost approach, that methanol is used as additive into Zn2+‐containing electrolyte for long‐life Zn ion batteries, was developed. Methanol can mix with water in any ratio through the formation of hydrogen bonds, which participates in the solvation shell of Zn2+ ion in a manner of forming the [Zn(OH2)x(CH3OH)y]2+ cations. The interaction between Zn2+, methanol and water can effectively suppress the side reactions. As a result, Zn/Zn symmetric cell shows a long‐term stability for over 480 h at 1 mA cm−2 with 1 mAh cm−2. In addition, full battery based on the MnO2 cathode exhibits an improved capacity retention after 100 cycles at 0.1 A g−1 and an excellent electrochemical performance at low temperature. Easy electrolyte modification: Methanol is first employed as additive for Zn2+‐containing electrolyte for long‐life Zn ion batteries. Here, methanol can mix with water in any ratio through the formation of hydrogen bonds, which participates in the solvation shell of Zn2+ ion in a manner of forming the [Zn(OH2)x(CH3OH)y]2+ cations. The interaction between Zn2+, methanol and water can effectively suppress the side reactions.